Effectiveness of Village Fund Policy in Increasing Infrastructure Development in Balumbung Village, Tompobulu District, Bantaeng Regency - Titin Nurfadilla; Warda; Andi Hakib (Masterpiece, 2026)
Village Funds constitute one of the Indonesian government's primary policy instruments for promoting equitable rural development through infrastructure improvement and community empowerment. However, the effectiveness of Village Fund implementation varies across regions due to differences in governance capacity, community participation, and accountability. This study aims to evaluate the effectiveness of the Village Fund policy in enhancing infrastructure development in Balumbung Village, Tompobulu District, Bantaeng Regency. A qualitative descriptive approach was employed using primary data collected through observations, semi-structured interviews with village officials and community representatives, and documentation analysis. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings indicate that the Village Fund policy has been implemented effectively through participatory planning, transparent implementation, and collaborative supervision involving both the village government and local communities. Infrastructure projects, including road improvements, clean water facilities, drainage systems, and public utilities, have significantly improved accessibility, mobility, and residents' quality of life while supporting local economic activities. Nevertheless, several challenges remain, particularly implementation delays, limited administrative capacity, budget constraints, and the need for stronger transparency mechanisms. The study concludes that the effectiveness of Village Fund policy depends not only on financial allocation but also on participatory governance, institutional capacity, and continuous public oversight. These findings contribute to the literature on rural development and public policy implementation by providing empirical evidence from an Indonesian village context and offering policy recommendations to strengthen sustainable infrastructure development and village governance.